Branched Chain Amino Acids (BCAAs) and Traumatic Brain Injury: A Systematic Review. Issue 1 (January 2018) - Sharma, Bhanu; Lawrence, David W.; Hutchison, Michael G.
Abstract : Background: Despite the prevalence of traumatic brain injury (TBI), pharmaceutical treatment options for brain injury remain limited. However, nutritional intervention (such as with branched chain amino acids [BCAAs]) has emerged as a promising treatment option for TBI. Objectives: (1) To determine whether TBI patients have lower levels of endogenous BCAAs postinjury; and (2) to evaluate whether post-TBI BCAA supplementation improves clinical outcome. Design: A systematic review of primary research articles examining the relationship between BCAAs and TBI recovery indexed in Ovid/MEDLINE, EMBASE, and PsycINFO. Results: Of the 11 studies identified, 3 examined the effects of TBI on endogenous BCAA levels and consistently reported that BCAA concentrations were depressed postinjury. The remaining 8 studies examined the effects of BCAA supplementation on TBI outcome in animals ( n = 3) and humans ( n = 5). The animal studies (in mild-to-moderate TBI) showed that BCAAs improved post-TBI outcome. Similar results were found in human trials (conducted primarily in patients with severe TBI), with 4 of the 5 studies reporting improved outcome with BCAA supplementation. Conclusion: Although our review demonstrates an overall positive association between BCAAs and TBI outcome, the evidence of the efficacy of supplementation has been limited to severe TBI. To date, there is insufficient evidence to determine the benefits of BCAAs in mild TBI. Given the high frequency of mild TBI and the promise of BCAAs as an intervention in severe TBI, future research should examine the effects of BCAAs in milder brain injury.